Strategi Implementasi Pendidikan Spiritual Quotient Dalam Meningkatkan Akhlak Mulia di MAN 2 Blitar - Arifin, M. Samsul; Jauhari, Moh. Irmawan (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2025)
This research aims to analyze strategies for implementing spiritual intelligence in education as an effort to improve noble morals as well as being a role model for other educational institutions. This research was conducted at the Tunas Pratama Community Learning Activity Center, Blitar City with a descriptive qualitative method using a case study approach. Data was collected through in-depth interviews, participant observation and documentation. The research results show that the strategy for implementing spiritual quotient education at MAN 2 Blitar includes three stages, namely 1) strategic analysis using the environment and determining the formulation of mission, goals and policies; 2) implementation of spiritual education quotient with various programs managed by the religious team; 3) evaluation and control using direct and practical techniques.